Selective sensing and visualization of pesticides by ABW-type metal–organic framework based luminescent sensors. Issue 66 (25th November 2019) - Di, Ling; Xia, Zhengqiang; Li, Jian; Geng, Zhongxing; Li, Chun; Xing, Yang; Yang, Zhanxu
Abstract : A novel ABW-type luminescent metal–organic framework was applied for selective visualization sensing of trace amounts of 2, 6-dichloro-4-nitroaniline and vapor sensing of trifluralin. Abstract : A new ABW-type luminescent metal–organic framework (MOF) namely (H3 O)[Zn2 L(H2 O)]·3NMP·6H2 O (1 ), constructed with eco-friendly Zn 2+ and the multicarboxylate intraligand (LH5 ) was designed, synthesized and fully characterized by X-ray single-crystal diffraction, steady-state absorption and emission spectroscopy, and SEM observations. The MOF-based suspension sensor 1 (NMP) demonstrated high sensitivity to low-concentration pesticides of chlorothalonil (CTL), nitrofen (NF), trifluralin (TFL), and 2, 6-dichloro-4-nitroaniline (DCN), which was assigned to the synergistic effect of the photoinduced electron transfer and the fluorescence resonance energy transfer. With the highest luminescent detection efficiency ( K SV up to 11.194 μmol −1 and LOD down to 2.93 ppm) to DCN, 1 (NMP) was successfully applied for the selective sensing of DCN. The MOF-based film sensor 1 (film) illustrated the selective visualization sensing of trace amounts of DCN. In addition, based on the high saturated vapor pressure of TFL and the unique bathochromic shift effect to the emission maxima of 1, the MOF-based luminescent vapor sensing device 1 (LED) successfully exhibited operability for sensing of TFL vapor. The results illustrated a feasible approach to construct new MOF-based luminescent sensors for selective sensing and visualization of pesticides.